The Soviet Repression Policy, its influence on karakalpak women’s lives and their results - Atamuratovna, Abdullayeva Yaxshibeka (International Journal of Psychosocial Rehabilitation, 2020)
Today in the Republic of Uzbekistan a great attention is being paid to the honouring the names of repression victims, who died in the struggle for independence, for national freedom. The government adopted some decrees, mainly “On perpetuating the names of activists who died in the struggle for people’s freedom and Motherland” adopted on 12 May, 1999 («People’s voice», June 23, 1999); “On appointing the day of remembrance of the repression victims” adopted on 1 May, 2001 («People’s voice», May 2, 2001). The Soviet repression policy influenced on the lives of females as well. Generally, the oppression of the population who are against the system of colonial governing is the peculiar characteristics of any aggressive colonial policy.